2006
DOI: 10.1097/01.ccm.0000218807.20570.c2
|View full text |Cite
|
Sign up to set email alerts
|

Local activation of the tissue factor-factor VIIa pathway in patients with pneumonia and the effect of inhibition of this pathway in murine pneumococcal pneumonia*

Abstract: These data suggest that TF-FVIIa activity contributes to activation of coagulation in the lung during pneumococcal pneumonia but does not play an important role in the antibacterial host defense in this murine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
93
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 41 publications
8
93
2
Order By: Relevance
“…43 We also note that others have reported a "paradoxically" increased granulocyte accumulation in the lung of mice with reduced hematopoietic TF expression 44 (which would be consistent with the enhancing effect of reduced Irf8 expression on granulopoiesis 38,45 ), whereas pharmacologic targeting of the ternary TF-VIIa-Xa complex with NapC2 (which blocks TF-initiated coagulation activation, but preserves TF-EPCR-PAR2 signaling, as shown in Figure 3C-D) had no such effects. 46,47 The described contributions of TF, EPCR, and PAR2 to the normal integration of TLR4-and interferon-regulated gene expression extend the biological rationale for the mechanistic coupling of inflammation and TF-mediated coagulation activation. Traumatic inflammatory states.…”
Section: Discussionmentioning
confidence: 99%
“…43 We also note that others have reported a "paradoxically" increased granulocyte accumulation in the lung of mice with reduced hematopoietic TF expression 44 (which would be consistent with the enhancing effect of reduced Irf8 expression on granulopoiesis 38,45 ), whereas pharmacologic targeting of the ternary TF-VIIa-Xa complex with NapC2 (which blocks TF-initiated coagulation activation, but preserves TF-EPCR-PAR2 signaling, as shown in Figure 3C-D) had no such effects. 46,47 The described contributions of TF, EPCR, and PAR2 to the normal integration of TLR4-and interferon-regulated gene expression extend the biological rationale for the mechanistic coupling of inflammation and TF-mediated coagulation activation. Traumatic inflammatory states.…”
Section: Discussionmentioning
confidence: 99%
“…We measured circulating levels of a select group of coagulation markers thought to be important in the coagulation response to infection (28,(37)(38)(39). In addition to the changes we observed, changes may well occur at the local level (31,40) or within other coagulation system components or factors that are not reflected in our selection of biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Local activation of the coagulation system is known to occur in pneumonia, with fibrin deposition in the alveolar compartment helping to contain infection but also enhancing vascular permeability, stimulating proinflammatory cytokines, and promoting neutrophil accumulation (31). This local coagulation activation appears to be driven primarily by tissue factor (32).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier it has been demonstrated that pulmonary coagulopathy is an important feature of pulmonary infection (38,39), with changes in fibrin generation being restricted to the site of infection in patients with community-acquired pneumonia caused by S. pneumoniae (46) or ventilator-associated pneumonia caused by several pathogens, among others P. aeruginosa (47,48). Pulmonary coagulopathy now gains more and more interest as a new target in therapeutic studies of acute lung injury of pneumonia (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%